(untitled) (SciComm Report, 2021)
The impact of the global health crisis caused by COVID-19 generated in the educational system an anticipated change from the “face-to-face” paradigm to the “virtual” one whose impact seems to be more forceful depending on whether students and teachers have sufficient resources available as to access the necessary infrastructure that guarantees the right to education. The article set out to investigate the fundamental digital competencies of university students from a public institution through the creation of a sample of students taking two different undergraduate courses. The applied methodology was descriptive transversal type. An online instrument was designed which was answered by 56 students. Data was processed for descriptive statistical processing, could be quantitatively inferred and individuals characterized in relation to certain aspects that affect a digital divide typology: connectivity, availability of relevant communication and computer equipment, and knowledge of synchronous and asynchronous tools in a learning environment or virtual classroom. The main results indicate that there are gaps in use and access. The average number of computers per home was 1.5 (SD of 0.92) for an average of 4.1 (DS of 2.24) people living together. 47% of students reported regular or poor connectivity, while 67% reported accessibility issues to the institutional virtual classroom, despite 66% reporting how to manage them. 83% of teachers used digital platforms complementary to institutional ones. The article enables its replication in other educational areas (for example, in the teaching sector, administrative and teacher personnel), strengthening projects in information and communication technologies to have trained human capital in the face of possible emerging ones.